Seroprevalence, epidemiological factors, and spatial patterns of exposure to Trypanosoma cruzi in urban cats in Maceió, Northeastern Brazil - Iranilda Cotrim da Costa; Leila Maria Rosa dos Santos; Allana de Paula Castilho; Gabriela de Lima Rodrigues Pinto; Vitória Maximiana Soares dos Santos; Gismelli Cristiane Angeluci; Hélio Langoni; Simone Baldini Lucheis; Jonatas Campos de Almeida (The Veterinary Journal, 2026)

Comprehensive chemical and multivariate characterization of Amazonian guarana (Paullinia cupana) seed coats: Insights for sustainable valorization - Maria Paula Pimenta Vilas Boas; Simone de Nazaré Melo Ramos; Marcos Fellipe da Silva; Natalia Costa da Silva; Michel Rocha Baqueta; Joyce Grazielle Siqueira Stürmlinger; Tatiane Pereira de Souza; Helena Teixeira Godoy; Rosana Goldbek Coelho; Priscilla Efraim; Juliana Azevedo Lima Pallone (Food Research International, 2026)

Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Sheep breed-specific response to environment challenge against Haemonchus contortus and effect on immuno-hematological parameters - Cintia Hiromi Okino; Hornblenda Joaquina Silva Bello; Simone Cristina Méo Niciura; Amanda Freitas da Cunha; Estevão Camilo da Costa; Emanuelle Martins de Campos; Rafaela Tami Ikeda Kapritchkoff; Lorrane Gabriele Pinheiro Corrêa; Alessandro Pelegrine Minho; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Research Communications, 2026)
Variable resistance to Haemonchus contortus infection and the associated immune mechanisms have been investigated and characterized in different sheep breeds adapted to tropical climates. In a recent study, we compared the local immune responses of the resistant Santa Inês with those of the susceptible White Dorper and Texel sheep breeds under chronic haemonchosis, and evaluated the correlations of immune-related transcripts and different parasitic stages and sexes. The aim of present study was to further elucidate the immune mechanisms among these sheep breeds by comparing local responses, microscopic lesions in the abomasum and hematological parameters in lambs raised under varying levels of parasitic challenge. The naturally resistant Santa Inês breed maintained similar phenotypic characteristics across different levels of parasitic infection loads, whereas White Dorper and Texel breeds exhibited increased susceptibility under moderate to high challenge. Texel lambs showed altered mean corpuscular volume, indicative of macrocytic anemia, and also displayed the lowest resistance under low challenge conditions. Significantly higher levels of eosinophils, lymphocytes and monocytes in peripheral blood, along with increased expression of Galectin-11 gene in the abomasum, were observed in Santa Inês sheep compared to the other breeds. These responses may represent key host mechanisms contributing to improved control of infection. Overall, our findings demonstrate that resistance to H. contortus infection is breed-dependent and modulated by environmental parasite challenge, providing insights that may forward to the targeted strategies for sheep flock management.

Moraxella species isolated from blood cultures in Europe (MORAXEu): a multicentre study of epidemiology and antimicrobial susceptibility with complementary phylogenomic analysis of publicly available genomes - Tone Tønjum; Vinicius da Silva Franklin-Duarte; Johan Christian Berild; Konstantina Gartzonika; Eirini Christaki; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Nikolaos Giormezis; Gergana Lengerova; Yordan Kalchev; Ana Budimir; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Cryopreservation-induced proteomic alterations in Pêga donkey (Equus asinus) spermatozoa - Camilo Jose Ramirez-Lopez; Isabella Cristina Tolêdo Alves Costa; Wassali Valadares de Sousa; Yara Martins da Silva; Faider Alberto Castano Villadiego; Tayna Bolsam da Silva; Renner Philipe Rodrigues Carvalho; Arabela Guedes de Azevedo Viana; Jose Carlos Montes-Vergara; Mariana Machado-Neves; Simone Eliza Facioni Guimaraes; Fabio Cesar Sousa Nogueira; et al. (Cryobiology, 2026)

Virome of neotropical Sabethes mosquitoes reveals two novel viruses in the Spiciviridae family - Endrya do Socorro Foro Ramos; Lilian de Oliveira Guimaraes; Geovani de Oliveira Ribeiro; Marcos Anicete Santos; Ramendra Pati Pandey; Simone Luchetta Reginato; Juliana Telles-de-Deus; Eduardo Sterlino Bergo; Luis Filipe Mucci; Vera Lucia Fonseca de Camargo-Neves; Antonio Charlys da Costa; Elcio Leal; et al. (Virus Genes, 2026)
The family Spiciviridae , belonging to the order Ghabrivirales , is currently composed of only one officially recognized genus, Spicivirus . However, metagenomic studies have revealed an increasing diversity of related viruses, suggesting that the current classification may underestimate their evolutionary complexity. In this context, the aim of the present study was to detect and characterize new viruses related to the Spiciviridae in the family Culicidae mosquitoes. A total of nineteen mosquito pools were sequenced and analyzed using metagenomic approaches and bioinformatics tools. Among these, two novel viruses were identified in four pools (S4, S11, S18, and S19), provisionally named Sabethes virus 1 (SV1) and Sabethes virus 2 (SV2). Phylogenetic inference revealed clades with strong statistical support and genetic divergences greater than 20% in the RNA-dependent RNA polymerase (RdRp) protein. These findings contribute to a detailed analysis of the genomic diversity associated with Spiciviridae . Although Spicivirus is currently the only genus officially recognized, our results suggest the presence of viruses that may represent new taxonomic groupings not yet described by the ICTV.

Potential of Composted Macrophytes as a Sustainable Organic Fertilizer: Environmental and Agronomic Insights - Paulo Sergio Costa Trindade; André Luiz de Freitas Espinoza; João Henrique Silva da Luz; Ingrid Martins Stelutti; André Luis Pirotello; Adriana Sturion Lorenzi; Simone Raposo Cotta; Paulo Sergio Pavinato; Tiago Tezotto (Journal of Soil Science and Plant Nutrition, 2026)
This study evaluated the agronomic potential and environmental impact of a macrophyte-based fertilizer (OMF) in maize cultivation. OMF was previously characterized in accordance with regulatory standards and applied to sandy loam and clayey soils at six rates (0, 2, 4, 6, 8, and 10 g dm⁻³). The experimental design also included a mineral fertilizer (MF) control receiving N, P, and K amounts equivalent to the 10 g dm⁻³ application, arranged in a randomized block design. After 45 days in greenhouse conditions, maize biomass and total nutrient accumulation, soil macronutrient concentrations, and the activities of arylsulfatase, β-glucosidase, and acid phosphatase were quantified. Basal soil respiration (BSR) and nutrient leaching were also evaluated through laboratoy-based analyses. OMF increased BSR, with CO₂ release in sandy loam and clayey soils highest under OMF (11.5; 10.7 mg g⁻¹), moderate under sludge compost (7.06; 7.51 mg g⁻¹), and lowest in unfertilized soil (2.34; 3.40 mg g⁻¹). OMF also promoted linear increases in soil P, K, Ca, Mg, and S, as well as in maize biomass and total N, P, and K accumulation. However, the highest OMF dose achieved only 20–31% of MF biomass. Moreover, organic fertilizers consistently reduced NO₃⁻-N, NH₄⁺-N, and K⁺ leaching compared with MF. In sandy soil, NO₃⁻-N leaching decreased by 31.2% and 38.5%, NH₄⁺-N by 45.6% and 37.4%, and K⁺ by 71.3% and 24.3% under SSC and OMF, respectively. In clayey soil, reductions reached 44.6% and 46.4% for NO₃⁻-N, 24.0% and 20.9% for NH₄⁺-N, and 35.9% and 15.7% for K⁺ under SSC and OMF, respectively. OMF offers environmental advantages by decreasing NO₃⁻-N leaching and supplying a slow-release K⁺ source, although it remains less effective than mineral fertilizer in promoting maize growth.

Abscisic Acid Modulates Physiological and Proteomic Changes During Histodifferentiation and Germination of Somatic Embryos in Euterpe edulis - Débora Pellanda Fagundes; Joana Silva Costa; Jociel Nascimento de Noronha; Mateus Santana Rodrigues; Caroline Palacio de Araujo; Simone Wellita Simão de Carvalho; Ingridh Medeiros Simões; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; Elias Terra Werner; Marcia Flores da Silva Ferreira; Amir Ali Khoddamzadeh; et al. (Journal of Plant Growth Regulation, 2026)
Euterpe edulis Martius (juçara palm) is an endangered species of high ecological and economic importance. Its propagation via reproduction is limited by the recalcitrance of its seeds, which hinders conservation and genetic improvement. Somatic embryogenesis represents an efficient alternative for large-scale clonal propagation and conservation. The present study evaluated the effect of abscisic acid (ABA) on histodifferentiation and germination of somatic embryos, to optimize in vitro regeneration of E. edulis . High rates of histodifferentiation (~ 98%) and germination (~ 95%) were achieved with 5 µM ABA, resulting in vigorous embryos with well-developed haustoria. Higher ABA concentrations (10–15 µM) were associated with reduced germination and delayed developmental progression, whereas the absence of ABA impaired histodifferentiation and embryo vigor. Proteomic profiling revealed increased accumulation of structural proteins (β-TUB7, TUBB1, TUBB5), chaperones (HSP83), proteasome components (PSMA2-like), energy metabolism enzymes (GAPDH2, PFK, PFP-α), tricarboxylic acid/glyoxysomal enzymes (SDH5, MDH-glyox), and nitrogen/methylation enzymes (GS, AHCY) in embryos treated with 5 µM ABA, suggesting associations with cytoskeletal remodeling, mitochondrial stability, epigenetic adjustments, and selective translation. In contrast, a decrease in defense proteins such as PR1 reflected a typical developmental trade-off. ABA also involves the integration of hormonal adjustments and the regulation of antioxidant enzymes. In summary, 5 µM ABA promotes efficient histodifferentiation and germination of embryos, enabling in vitro cloning, conservation, and genetic improvement of the species.

Copper and lead trigger distinct responses in two Brazilian mosses - Mateus Fernandes Oliveira; Tiago Vilas-Boas; Felipe Della-Torre; Najla Meireles-Medeiros; Raphael Ricon de Oliveira; Marcel Giovanni Costa França; Lucas Anjos Souza; Adaíses Simone Maciel-Silva (Theoretical and Experimental Plant Physiology, 2026)
Metal contamination, particularly by copper (Cu) and lead (Pb), is a persistent environmental threat, yet the adaptive responses of Neotropical bryophytes to such stressors remain largely unexplored. This study evaluated biomass production, photosynthetic performance, and metal accumulation in two native Brazilian mosses ( Campylopus savannarum (Müll.Hal.) Mitt. and Polytrichum juniperinum Willd. ex Hedw.) exposed to increasing concentrations of Cu and Pb under controlled laboratory conditions. We hypothesized that their contrasting morpho-anatomical traits, especially differences in lamellae structure, photosynthetic surface organization, and the presence of conduction tissues, would lead to distinct physiological strategies of metal tolerance. At the end of 240 days, biomass and maximum quantum efficiency of PSII ( Fv/Fm ) were assessed, and tissue metal concentrations were quantified. The moss P. juniperinum exhibited remarkable tolerance, maintaining stable biomass and photosynthetic capacity across all treatments, while C. savannarum presented pronounced declines, especially under high Pb exposure. Both species displayed dose-dependent metal accumulation but with distinct patterns: C. savannarum accumulated nearly 196-fold more Cu at the highest treatment compared to the control, whereas P. juniperinum stored about 44-fold more Pb than the control. These contrasting responses likely reflect species-specific strategies of metal tolerance. These results position Neotropical mosses as valuable bioindicators and potential agents for generating genomic data to improve our understanding of metal tolerance in bryophytes. Future research should investigate tissue-concentration metal partitioning and the molecular mechanisms underlying tolerance in native Brazilian bryophytes.

Proteomic profile associated with the m aturation of somatic embryos of Euterpe edulis under polyamine treatments in material derived from a single mother plant - Joana Silva Costa; Débora Pellanda Fagundes; Mateus Santana Rodrigues; Tamyris de Mello; Jociel Nascimento de Noronha; Ingridh Medeiros Simões; Simone Wellita Simão de Carvalho; Tadeu Ériton Caliman Zanardo; Claudete Santa-Catarina; Edilson Romais Schmildt; Amir Ali Khoddamzadeh; José Carlos Lopes; et al. (Journal of Plant Growth Regulation, 2026)
Euterpe edulis is of ecological and economic relevance and is currently threatened with extinction. Its vulnerability to extinction, combined with the recalcitrant nature of its seeds, justifies the search for alternative reproduction techniques. Somatic embryogenesis is an alternative propagation method that is subdivided into distinct phases. Maturation is a crucial phase in the process for the successful regeneration of somatic plantlets. Therefore, this study aimed to investigate the effects of putrescine and spermidine, applied individually or in combination, on the maturation of E. edulis somatic embryos originating from a single mother plant. To this end, concentrations of putrescine (0, 500, 1000, or 1500 µM) and spermidine (0, 150, 200, 250, 300, or 350 µM) were analyzed. The highest number of somatic embryos (71.67) and coleoptilar embryos (67.67), both per embryogenic callus, was obtained in maturation medium supplemented with spermidine (350 µM) + putrescine (1500 µM). In this treatment, 313 differentially accumulated proteins (DAPs) were identified, with 63 up -accumulated and 250 down -accumulated compared to the control (without supplementation). Functional annotation by orthology suggests that among the DAPs, some proteins stand out for being potentially associated with the following biological processes: cell defense, energy metabolism, carbon/nitrogen balance equilibrium, and regulation of the cellular redox environment. It is concluded that spermidine (350 µM) + putrescine (1500 µM) enhances the formation of E. edulis somatic embryos derived from a single mother plant and the transition of these embryos to the coleoptilar development stage. These responses were accompanied by proteomic changes suggesting conserved biological processes potentially associated with embryo maturation.

Organic matter, microplastics and macrofaunal communities associated with Posidonia oceanica meadows - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Francesca Garaventa; Simone Mirto; Francesca Ape (Marine Environmental Research, 2026)

Opuntia mucilage as a food ingredient: a systematic and bibliometric review of technological and functional applications - Diego Araujo da Costa; Ziane da Conceição das Mercês; Cecília Roratto Köhn; Simone Hickmann Flôres; Alessandro de Oliveira Rios (Food Bioscience, 2026)

Assessment of Translocation of Lacticaseibacillus rhamnosus CGMCC 1.3724 Radiolabeled with Technetium-99 m Isotope in an Experimental Model of Immunosuppression - Nayara Salgado Vieira Sette; Maria Emília Rabelo Andrade; Luísa Martins Trindade; Amanda Dias Borges; Carla Carolina Martins Carneiro; Bárbara Gatti Cardoso; Simone Odília Antunes Fernandes; Bruno Galloti; Flaviano dos Santos Martins; Paola Caroline Lacerda Leocádio; Jacqueline Isaura Alvarez-Leite; Geovanni Dantas Cassali; et al. (Probiotics and Antimicrobial Proteins, 2026)

A comparison of two vitrification methods and the effect of dimethyl sulfoxide in vitrification solution for cryopreservation of Euterpe edulis Martius (Arecaceae) - Débora Pellanda Fagundes; Joana Silva Costa; Ingridh Medeiros Simões; Simone Wellita Simão de Carvalho; Caroline Palacio de Araujo; Lana Laene Lima Dias; Eduardo Alves; Elias Terra Werner; Edilson Romais Schmildt; Amir Ali Khoddamzadeh; Wagner Campos Otoni; Rodrigo Sobreira Alexandre (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Euterpe edulis Martius (Arecaceae) is a native species of the Atlantic Forest hotspot with ecological and economic relevance. Its fruits contribute to biodiversity maintenance by feeding birds and mammals and are valued for their antioxidant properties and applications in the food and cosmetic industries. However, habitat loss and propagation constraints have contributed to the threatened status of this species, reinforcing the need for complementary ex situ conservation strategies. Thus, this study evaluated the cryopreservation of somatic embryos of E. edulis using conventional vitrification and droplet vitrification in association with a modified Plant Vitrification Solution 3 (PVS3) supplemented with different concentrations of dimethyl sulfoxide (DMSO; 0, 5, 10, and 15%). No significant differences were observed between vitrification methods regarding post-thaw recovery. However, PVS3 supplemented with 10% and 15% DMSO promoted higher survival than 0% and 5%, with maximum values recorded at 15% DMSO (67.50% in droplet vitrification and 69.50% in conventional vitrification). Scanning electron microscopy revealed greater structural alterations in somatic embryos at more advanced maturation stages after cryopreservation, whereas transmission electron microscopy showed treatment-dependent differences in cellular ultrastructure, including vacuolization, cell wall disruption, and preservation of nuclear organization in surviving cells. Elemental analysis by energy-dispersive X-ray spectroscopy (EDS) revealed differences among cryopreservation treatments, with higher carbon intensity observed in treatments showing greater post-thaw survival and lower carbon intensity associated with reduced survival. This technique demonstrates potential for preserving germplasm of endangered E. edulis adult plants and can strategically support genetic improvement programs.

Chemical characterization and antinociceptive and anti-inflammatory activities of the aqueous extract of Myrciaria floribunda (H. West ex Willd.) O. Berg fruit peel - Simone Patricia De Freitas Rosa; Izabelly Bianca da Silva Santos; Wendel César eSilva Pereira; Thaís Vitória Freitas de Souza; Paulo Henrique Eloi Fernandes; Gabriela Ribeiro de Sousa; José Fernandes da Silva Cardoso; Alisson Macário de Oliveira; Márcia Vanusa da Silva; Wêndeo Kennedy Costa; Maria Tereza dos Santos Correia (Inflammopharmacology, 2026)
Natural products derived from medicinal plants represent an important source of bioactive compounds with potential therapeutic applications in the management of pain and inflammatory disorders. In this study, the chemical profile and pharmacological activities of the aqueous extract obtained from the fruit peel of Myrciaria floribunda (AeMf) were investigated. Chemical characterization was performed using high-performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC–ESI–MSⁿ). The antinociceptive activity of AeMf was evaluated in mice using acetic acid–induced abdominal writhing, formalin, and tail immersion tests, while the anti-inflammatory potential was assessed through carrageenan-induced paw edema and peritonitis models. Chromatographic analysis revealed a chemical profile predominantly composed of organic acids and related metabolites, including quinic acid, citrate, maleate, and a fatty acid hexoside. In nociceptive models, AeMf produced a significant and dose-dependent reduction in acetic acid–induced writhing and markedly decreased paw-licking behavior in both phases of the formalin test. In addition, the extract increased tail withdrawal latency in the thermal nociception assay, indicating the involvement of both peripheral and central analgesic mechanisms. In inflammatory models, AeMf significantly inhibited carrageenan-induced paw edema, reduced leukocyte and neutrophil migration to the peritoneal cavity, and markedly suppressed the production of pro-inflammatory cytokines, including TNF-α and IL-1β. Collectively, these findings demonstrate that AeMf exerts potent antinociceptive and anti-inflammatory effects, likely mediated through the modulation of inflammatory mediators and cellular recruitment. The results highlight the therapeutic potential of Myrciaria floribunda as a promising natural source of bioactive compounds for the development of novel strategies for pain and inflammation management.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Comparative performance of CTG-3D and resazurin assays in low-density gelatin-alginate bioprinted mesenchymal stromal cell constructs - Isabela Souza Marques; Maria Eduarda Oliveira Borges; Manuela Abrantes do Rego; Karina Ribeiro Silva Pereira; Genilza Pereira de Oliveira; Débora dos Santos Ornellas; Erika Afonso Costa Cortez Marques; Alessandra Alves Thole; Simone Nunes de Carvalho (In vitro models, 2026)

Radioactivity behavior in hydrothermal volcanic systems: Preliminary in situ investigations at high and low gas flux degassing areas - Giordano Bufi; Silvia Massaro; Francesco Giordano; Pierfrancesco Dellino; Silvia Raino’; Alessandro Aiuppa; Giulio Bini; Stefano Caliro; Davide Cerasole; Antonio Costa; Fabio Dioguardi; Danilo Elenterio; et al. (Journal of Environmental Radioactivity, 2026)

Wyeomyia confusa Lispivirus (WcLispV-SP): a novel neotropical mosquito virus in the Lispiviridae family - Lilian de Oliveira Guimarães; Roseane da Silva Couto; Simone Luchetta Reginato; Luis Filipe Mucci; Ramendra Pati Pandey; Vera Lucia Fonseca de Camargo-Neves; Antonio Charlys da Costa; Karin Kirchgatter; Elcio Leal (Archives of Virology, 2026)
Metatranscriptomic analysis of Wyeomyia confusa mosquitoes collected in the Atlantic Forest (Pindamonhangaba, São Paulo, Brazil) led to the identification of a previously uncharacterized virus, designated Wyeomyia confusa Lispivirus (WcLispV-SP), classified within the family Lispiviridae , genus Canmovirus . The viral genome consists of a negative-sense single-stranded RNA (ssRNA−) of 12,698 nucleotides, encoding six open reading frames (ORFs): nucleoprotein (N), two hypothetical proteins (HP/1 and HP/2), glycoprotein (G), ORFan protein, and RNA-dependent RNA polymerase (RdRp-L). Phylogenetic analysis supports the classification of WcLispV-SP as a distinct species within the genus Canmovirus . Structural analysis of the RdRp revealed conserved domains and catalytic motifs characteristic of members of the order Mononegavirales , supporting its functional integrity. These findings expand the known diversity of the Lispiviridae family and highlight the utility of metagenomic approaches for the discovery and characterization of RNA viruses associated with Neotropical sylvatic mosquitoes.

Intensified tropical pasture-based beef cattle production systems and their effects on carcass traits, meat quality and methane emissions from Nellore steers - Gabriele Voltareli da Silva; Rolando Pasquini Neto; Mariana Nunes Vieira de Melo; Luiza Budasz de Andrade; Althieres José Furtado; Ester Costa Fabricio; Analisa Vasques Bertoloni; Annelise Aila Gomes Lobo; Flavio Perna Junior; Sérgio Raposo de Medeiros; Alexandre Berndt; Renata Tieko Nassu; et al. (Livestock Science, 2026)

Sunshine Duration in Brazil From Meteosat (1983–2020): Climatology, Variability and Long‐Term Trends - Maria Lívia Lins Mattos Gava; Simone Marilene Sievert da Costa; Íris Paraguay Silva (International Journal of Climatology, 2026)
Sunshine duration (SDU) is a fundamental climatological variable with broad applications in agriculture, energy, health and tourism. However, despite its importance, Brazil lacks comprehensive country‐scale assessments, mainly due to deficiencies in the irregular and sparse in situ observation network. To overcome these limitations, this study employed the high‐resolution satellite‐based CMSAF SARAH‐3.0 SDU dataset for the 1983–2020 period, enabling a spatially consistent evaluation across Brazil. The analysis combined regional and gridded climatologies, Empirical Orthogonal Function (EOF) decomposition and robust trend assessment. Climatological results reveal strong regional contrasts: the Northeast records the highest and most regular SDU, while the South exhibits the lowest values. The largest (smallest) seasonal amplitude occurs in the North (Southeast). Also, the Central‐West exhibits a marked monsoonal cycle. EOF analysis identifies three leading modes of variability, associated with the South American Monsoon System, the Atlantic Intertropical Convergence Zone and a regional mode linked to intraseasonal variability over southeastern Brazil, the La Plata Basin and the adjacent South Atlantic. Long‐term analyses indicate generalised increases in SDU, with statistically significant positive trends in the Central‐West and Northeast, while the North and South display weaker and spatially heterogeneous tendencies. These findings fill a critical gap in Brazil's SDU climatology and underscore the need for continued monitoring to better understand the mechanisms driving observed changes and their implications for climate‐sensitive sectors.

Pharmaceuticals and cocaine in Brazilian seafood: An integrated weight-of-evidence assessment of bioaccumulation - Vinicius Roveri; Ursulla Pereira Souza; João Henrique Alliprandini da Costa; Jorge Luis dos Santos; Walber Toma; Simone dos Anjos Caivano; Alberto Teodorico Correia; Luciana Lopes Guimarães (Regional Studies in Marine Science, 2026)

Preliminary evaluation of the larvicidal, antioxidant, and toxicological activity of the lyophilized hydroethanolic extract of Croton argenteus against Aedes aegypti - Rafaela Brito Ribeiro Santos; Isabelly Domiciano Santos Guimarães; Yane Neves Valadares; Joane Cristina Costa Pereira; Daniel Lobo Sousa; Widarlane Ângela da Silva Alves; Debora Cardoso da Silva; Simone Andrade Gualberto; Eduardo Carvalho Lira; Janaina Silva Freitas (Biocatalysis and Agricultural Biotechnology, 2026)

Assessment of acute dermal toxicity of Croton pulegiodorus Baill. leaf essential oil in mice - Patryck Érmerson Monteiro dos Santos; Matheus Cavalcanti de Barros; Thaís Paes de Freitas; Amanda Vieira de Barros; Juliane Nancy de Oliveira Silva; Simone da Paz Leôncio Alves; Juliano Matheus de Lima Maux; Maria Betânia Melo de Oliveira; Thâmarah de Albuquerque Lima; Renata Mendonça Araújo; Jacinto da Costa Silva Neto; Thiago Henrique Napoleão; et al. (Toxicon, 2026)

Mentalis, DAO, and Platysma Muscles Treatment Using Botulinumtoxin A: A Multidisciplinary Italian Consensus Based on Literature Review - Salvatore Piero Fundarò; Giovanni Brunelli; Maria Cazzulani; Guido Dalla Costa; Roberto Dell’Avanzato; Roberta D’Emilio; Carlo Di Gregorio; Antonella Franceschelli; Paola Molinari; Monica Renga; Giovanni Salti; Adriano Santorelli; et al. (Toxicon, 2026)

The small mammal fauna (Marsupialia and Rodentia) from Araras ravine, a Quaternary deposit in northeastern Brazil, and their paleoclimatic significance for South American paleoenvironments - Simone Baes das Neves; João Paulo da Costa; Maria Eduarda Pereira Mello de Carvalho Ventura; Julia Pinheiro do Nascimento; Kleberson de Oliveira Porpino; Hermínio Ismael de Araújo-Júnior (Quaternary International, 2026)

Optimization of lithium diffusion modelling in plagioclase: implications for the assessment of pre-eruptive timescales - Simone Costa; Matteo Masotta; Fabio Colle; Pier Paolo Giacomoni; Claudia D’Oriano; Patrizia Landi (Chemical Geology, 2026)

Brazil’s climate leadership paradox: hosting COP30 amid domestic environmental rollbacks - Daniela Debone; Ronan Adler Tavella; Mariana Vieira da Costa; Eliane Seiko Maffi Yamada; Flavio Manoel Rodrigues da Silva Júnior; Sandra de Souza Hacon; Paulo Artaxo; Simone Georges El Khouri Miraglia (International Environmental Agreements: Politics, Law and Economics, 2026)

Ecotoxicological effects of drilling cuttings waste from oil wells: sensitivity of soil invertebrates and plants - Dara C. M. V. P. da Cruz; Higor E. F. Lorin; Fabrielle P. dos Reis; Cibele A. de Costa; Simone B. da Fontoura; Heraldo N. de Souza; Everaldo Zonta; Júlia C. Niemeyer (Ecotoxicology, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Obtaining and characterizing bacuri (Platonia insignis) seed flour: a strategy for valuing fruit co-products from a sustainable food perspective - Simone Kelly Rodrigues Lima; Luiz Brito de Souza Filho; José Otávio Carvalho Sena de Almeida; José Moreira Tavares Neto; Michel Muálem de Moraes Alves; Arkellau Kenned Silva Moura; Antônia Maria das Graças Lopes Citó; Francisco Cardoso Figueiredo; Leandro Josuel da Costa Santos; Liduína Soares de Carvalho Mendes; André Filipe Sousa Loiola; Joyce Lopes Macedo; et al. (Food Chemistry, 2026)

Antibacterial, antifungal and flavor-enhancing properties of essential oils in tomato sauce: Bio-guided fractionation and microencapsulation of Origanum vulgare L. essential oil - Marta Pavarino; Simone Duarte de Oliveira Costa; Melícia Cíntia Galdeano; Patrizia Rubiolo; Renata Valeriano Tonon; Janine Passos Lima; Barbara Sgorbini; Humberto Ribeiro Bizzo (Food Control, 2026)

Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Interactions between Mycoplasma hyopneumoniae strains and the resident lung microbiota in swine - Leonardo Teófilo Toledo; Richard Costa Polveiro; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira; Fernanda Simone Marks (Veterinary Microbiology, 2026)

Is there a glymphatic pathway to environmental risk in neurodevelopmental disorders? - Maiara de Aguiar da Costa; Sofia Januário Bolan; Maria Fernanda Pedro Ebs; Simone Lespinasse Araújo; Cristiano Juliano Faller; Tatiana Barichello; Michael Aschner; Jaqueline da Silva Generoso; Cinara Ludvig Gonçalves (Neurotoxicology and Teratology, 2026)

The equilibrium of nutrition and protection in the interaction between Byrsonima coccolobifolia and Cecidomyiidae - Reisila Simone Migliorini Mendes; Elaine Cotrim Costa; Gracielle Pereira Pimenta Bragança; Rosy Mary dos Santos Isaias (Flora, 2026)

Generative artificial intelligence and marine ecological monitoring - Luciano Ortenzi; Jacopo Aguzzi; Damianos Chatzievangelou; Eugenio Nerio Nemmi; Michele Ferrari; Ivan Masmitja; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Giacomo Picardi; Paula Espina; Simona Violino; et al. (Environmental Modelling & Software, 2026)

Investigation of Phytol as an Inhibitor of the Efflux Pump (QacA/B) in Staphylococcus aureus: in silico and in vitro Studies - José Weverton Almeida-Bezerra; Carlos Alonso Leite dos Santos; Saulo Almeida Menezes; Cícera Datiane de Morais Oliveira-Tintino; Rafael Pereira da Cruz; Adrielle Rodrigues Costa; Janaína Esmeraldo Rocha; Daniel Sampaio Alves; Simone Galdino de Sousa; Ewerton Yago de Sousa Rodrigues; Gabriel Gonçalves Alencar; José Maria Barbosa Filho; et al. (Pharmaceutical Research, 2026)

Integrated in Vitro, in Vivo, Molecular Docking, and ADMET in Silico Assessment of β-Caryophyllene as a NorA Efflux Pump inhibitor in Resistant Staphylococcus Aureus (MRSA) - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Cícera Datiane de Morais Oliveira-Tintino; Adrielle Rodrigues Costa; Viviane Bezerra da Silva; Maria Flaviana Bezerra Morais-Braga; Irwin Rose Alencar de Menezes; Ana Carolina Ferreira Araujo; Lucas Yure Santos da Silva; Daniel Sampaio Alves; Guilherme Fernandes Teixeira; Lucas dos Santos Sa; et al. (Current Microbiology, 2026)

Occurrence of pharmaceuticals and cocaine in liver and muscle of different fish species from a Brazilian coastal zone - Vinicius Roveri; Ursulla Pereira Souza; João Henrique Alliprandini da Costa; Walber Toma; Simone dos Anjos Caivano; Alberto Teodorico Correia; Luciana Lopes Guimarães (Regional Studies in Marine Science, 2025)

Micronucleus assay in buccal and urothelial epithelial cells of wildland firefighters exposed to wildfire smoke - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; Stefano Bonassi; João Paulo Teixeira; et al. (Journal of Hazardous Materials, 2025)

Influence of seasonal climatic variation on volatile organic compounds of Drimys brasiliensis leaves and its impact on the antitumor activity - Gabrielle Cruz de Andrade; Wiliam de Lima; Simone Bernardes da Fontoura; Juliana Soares da Costa; Fabiano Silva Locks Júnior; Amanda Köche Marcon; Evelyn Winter; Cristian Soldi (Biochemical Systematics and Ecology, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Integrated use of histological and hormonal biomarkers to assess metal contamination in Leporinus friderici from mining areas in the Amazon - Breno Richard Monteiro Silva; Antonio Elivelton Paiva De Oliveira; Nathalia Nogueira da Costa de Almeida; Simone do Socorro Damasceno Santos; Rossineide Martins da Rocha; Maria Auxiliadora Pantoja Ferreira (Chemosphere, 2025)

Exploring endogenous lactic acid bacteria potential: Isolation to genetic insights on aromatic compounds - Daniel Kuhn; Caroline Schmitz; Gabriela Rabaioli Rama; Manuela Araujo Costa; Priscilla Romina De Gregorio; José Matías Irazoqui; Ariel Fernando Amadio; Angiolella Lombardi; Vera Lúcia Milani Martins; Daiane Heidrich; Simone Beux; Daniel Neutzling Lehn; et al. (Food Microbiology, 2025)

In vitro antioxidant activity and in vivo antinociceptive and anti-inflammatory effects of the hydroethanolic extract from leaves of Myrciaria floribunda (H. West ex Willd.) O. Berg in Swiss mice - Izabelly Bianca da Silva Santos; Simone Patricia de Freitas Rosa; Wendel César eSilva Pereira; Bruno Souza dos Santos; Natanael Teles Ramos de Lima; José Maria Barbosa Filho; Alisson Macário de Oliveira; Thiago Henrique Napoleão; Maria Tereza dos Santos Correia; Wêndeo Kennedy Costa; Marcia Vanusa da Silva (Inflammopharmacology, 2025)

Drivers of the geographical distribution of nematode-based indices across Europe - Doina Thais Constance Mani; Vera Leatitia Mulder; Carmen Vazquez Martin; Stefan Geisen; Raquel Campos-Herrera; Andrea Čerevková; Simone Cesarz; Marcel Ciobanu; Sofia R. Costa; Ron de Goede; Nico Eisenhauer; Louise Jackson; et al. (Applied Soil Ecology, 2025)

Application of generative artificial intelligence in the aquacultural sector - Chiara Fini; Simone Gaetano Amato; Daniela Scutaru; Sara Biancardi; Francesca Antonucci; Simona Violino; Luciano Ortenzi; Eugenio Nerio Nemmi; Alessandro Mei; Federico Pallottino; Simone Figorilli; Corrado Costa (Aquacultural Engineering, 2025)

Impact of wildfire emissions exposure on the associations between levels of lung injury, lipid peroxidation, DNA oxidation, and exposure biomarkers - Bela Barros; Ana Margarida Paiva; Rui Azevedo; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; João Paulo Teixeira; Solange Costa; Agostinho Almeida; et al. (Science of The Total Environment, 2025)

A European survey on anaerobes from paediatric blood cultures: a comparative analysis with adults - Matteo Boattini; Arianna Aceti; Paulo Bastos; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Vasileios Kakouris; Yordan Kalchev; Ana Budimir; Branka Bedenić; Zana Rubic; Monica Licker; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Environmental Impacts of Brazilian Beef Production and Mitigation Alternatives—A Systematized Review - Mariana Vieira da Costa; Daniela Debone; Simone Georges El Khouri Miraglia (Agricultural Research, 2025)

The effect of plastic pollution on coastal marine organisms – A systematic review - Thaiane Cantarino Costa; Beatriz Corrêa Thomé de Deus; Leslie Nascimento Altomari; Simone Jaqueline Cardoso (Environmental Monitoring and Assessment, 2025)

Post-weaning exposure to cannabidiol disrupts testicular cytoarchitecture and sperm quality in mice - Renata K. Carvalho; Maingredy R. Souza; Akemy N. Nishimura; Edvaldo M. Silva; Cinthia R.B. Silva; Francisco S. Guimarães; Monica L. Andersen; Simone M.T. Sabóia-Morais; Renata Mazaro-Costa (Reproductive Toxicology, 2025)

The oldest record of the family Iridinidae (Unionida): New fossil genera and species of bivalves from the Salvador Formation (Berriasian), Jatobá Basin, northeastern Brazil - Débora Eliza Baumann; Luiz Ricardo L. Simone; Rafael Costa da Silva; Renato Pirani Ghilardi (Journal of South American Earth Sciences, 2025)

Impact of occupational exposure to wildfire events on systemic inflammatory biomarkers in Portuguese wildland firefighters - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Joana Pires; Sandra Martins; Marta Oliveira; Josiana Vaz; Klara Slezakova; Maria do Carmo Pereira; Adília Fernandes; Simone Morais; et al. (Environmental Research, 2025)

Correction: Potential areas of occurrence for an invasive copepod in Brazil: a species distribution model approach - Pedro Henrique Menini Custodio; Thaiane Cantarino Costa; Nathália da Silva Resende; Lucas Rieger de Oliveira; Lucas Vieira Lima; Simone Jaqueline Cardoso (Hydrobiologia, 2025)

Potential areas of occurrence for an invasive copepod in Brazil: a species distribution model approach - Pedro Henrique Menini Custodio; Thaiane Cantarino Costa; Nathália da Silva Resende; Lucas Rieger de Oliveira; Lucas Vieira Lima; Simone Jaqueline Cardoso (Hydrobiologia, 2025)

Isolated Generalized Chorea in a Patient with Small-Expanded Allele Spinocerebellar Ataxia 17 - Giulia Paparella; Martina De Riggi; Simone Aloisio; Adriana Martini; Luca Angelini; Daniele Birreci; Davide Costa; Antonio Cannavacciuolo; Anna Maria Griguoli; Stefano Gambardella; Matteo Bologna (The Cerebellum, 2025)

Haemonchus contortus parasitic stages development and host immune responses in lambs of different sheep breeds - Cintia Hiromi Okino; Hornblenda Joaquina Silva Bello; Simone Cristina Méo Niciura; Gláucia Roberta Melito; Amanda Freitas da Cunha; Estevão Camillo da Costa; Emanuelle Martins de Campos; Rafaela Tami Ikeda Kapritchkoff; Alessandro Pelegrine Minho; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Immunology and Immunopathology, 2025)

Are trait responses of tree species across pyroregions indicative of fire-modulated plant functional strategies? - José Maria Costa-Saura; Gabriele Midolo; Carlo Ricotta; Mara Baudena; Carlo Calfapietra; Mario Elia; Paolo Fiorucci; Simone Mereu; Costantino Sirca; Donatella Spano; Gianna Vivaldo; Gianluigi Ottaviani (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

A physical parameterization for cloudy-sky downward longwave radiation: Validation for tropical and subtropical regions in Brazil - José Marcelo Lopes Júnior; Juan Carlos Ceballos; Simone Marilene Sievert da Costa; Francisco Luiz Leitão de Mesquita; Hallan Souza de Jesus; André Rodrigues Gonçalves (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Aluminum accumulation in mosses from the Brazilian savanna: a comparative study of two species revealing similar traits to vascular plants - Mateus Fernandes Oliveira; Ígor Abba Arriola; Guilherme Henrique Rodrigues-Mattos; Felipe Della Torre; Joni Esrom Lima; Marcel Giovanni Costa França; Rosy Mary dos Santos Isaias; Adaíses Simone Maciel-Silva (Planta, 2025)

Conspecific hyperparasitism in two Ornithodoros species (Ixodida: Argasidae) endemic to Brazil, and interspecific hyperparasitism between Amblyomma sculptum and Rhipicephalus microplus (Ixodida: Ixodidae) - Thiago F. Martins; Simone M. Simons; Caio Monteiro; Haile D. F. Chagas; Rafael A. Carvalho; Arthur M. Santana; Darci M. Barros-Battesti; Glauber M. B. de Oliveira; Livio M. Costa-Junior; Marcelo B. Labruna; Hermes R. Luz (Experimental and Applied Acarology, 2025)

Activation of the 20S proteasome core particle prevents cell death induced by oxygen- and glucose deprivation in cultured cortical neurons - Ivan L. Salazar; Michele Curcio; Miranda Mele; Rossela Vetrone; Simone Frisari; Rui O. Costa; Margarida V. Caldeira; Darci J. Trader; Carlos B. Duarte (Apoptosis, 2025)
Neuronal damage in brain ischemia is characterized by a disassembly of the proteasome and a decrease in its proteolytic activity. However, to what extent these alterations are coupled to neuronal death is controversial since proteasome inhibitors were shown to provide protection in different models of stroke in rodents. This question was addressed in the present work using cultured rat cerebrocortical neurons subjected to transient oxygen- and glucose-deprivation (OGD) as a model for in vitro ischemia. Under the latter conditions there was a time-dependent loss in the proteasome activity, determined by cleavage of the Suc-LLVY-AMC fluorogenic substrate, and the disassembly of the proteasome, as assessed by native-polyacrylamide gel electrophoresis followed by western blot against Psma2 and Rpt6, which are components of the catalytic core and regulatory particle, respectively. Immunocytochemistry experiments against the two proteins also showed differential effects on their dendritic distribution. OGD also downregulated the protein levels of Rpt3 and Rpt10, two components of the regulatory particle, by a mechanism dependent on the activity of NMDA receptors and mediated by calpains. Activation of the proteasome activity, using an inhibitor of USP14, a deubiquitinase enzyme, inhibited OGD-induced cell death, and decreased calpain activity as determined by analysis of spectrin cleavage. Similar results were obtained in the presence of two oleic amide derivatives (B12 and D3) which directly activate the 20S proteasome core particle. Together, these results show that proteasome activation prevents neuronal death in cortical neurons subjected to in vitro ischemia, indicating that inhibition of the proteasome is a mediator of neuronal death in brain ischemia.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Occupational exposure to wildland firefighting and its effects on systemic DNA damage - Filipa Esteves; Joana Madureira; Carla Costa; Joana Pires; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; et al. (International Journal of Hygiene and Environmental Health, 2025)

Could Exotic Birds Play a Significant Role in the Emergence of Antibiotic-Resistant Microorganisms? - Gabriel H. S. Britto; Lara R. Gomes; João P. Pimenta; Simone Sommerfeld; Maysa V. C. Silva; Phelipe A. B. M. Peres; Paula F. S. Braga; Letícia R. M. Costa; Isabelle E. Pedrosa; Márcio B. Bandarra; Terezinha Knöbl; Belchiolina B. Fonseca (Current Microbiology, 2025)

Applications and perspectives of Generative Artificial Intelligence in agriculture - Federico Pallottino; Simona Violino; Simone Figorilli; Catello Pane; Jacopo Aguzzi; Giacomo Colle; Eugenio Nerio Nemmi; Alessandro Montaghi; Damianos Chatzievangelou; Francesca Antonucci; Lavinia Moscovini; Alessandro Mei; et al. (Computers and Electronics in Agriculture, 2025)

Oral administration of cyantraniliprole to wistar rats during pregnancy and lactation alters maternal behavior and harms the female reproductive system of pubertal and adult offspring - Ana Camila Ferreira de Menezes; Karen Gomes Luiz; Julia Bandeira Velho; Débora Hipólito Quadreli; Ivana Regina da Costa; Letícia Pazin Bomfim; Maria Stacy dos Santos Silva; Simone Forcato Ferreira; Fábio Goulart de Andrade; Daniela Cristina Ceccatto Gerardin; Glaura Scantamburlo Alves Fernandes (Food and Chemical Toxicology, 2025)

Brazilian beef production and GHG emission – social cost of carbon and perspectives for climate change mitigation - Mariana Vieira da Costa; Daniela Debone; Simone Georges El Khouri Miraglia (Environmental Science and Pollution Research, 2025)

Substoichiometric La0.8MnO3-based nanocomposites for PGM-free activation of CH4: Ni or Cu? Surface or bulk? - Andrea Osti; Lorenzo Rizzato; Simone Costa; Jonathan Cavazzani; Antonella Glisenti (Fuel, 2025)

Watershed’s spatial targeting: Enhancing payments for ecosystem services to scale up agroecosystem restoration through nature-based solutions - Gislaine Costa de Mendonça; Maria Teresa Vilela Nogueira Abdo; Luis Miguel da Costa; Renata Cristina Araújo Costa; Fernando António Leal Pacheco; Milton Cezar Ribeiro; Maria José Brito Zakia; Laura De Simone Borma; Teresa Cristina Tarlé Pissarra (Ecosystem Services, 2025)

Glyphosate and glyphosate-based herbicides induce Poecilia reticulata to maintain redox equilibrium during and after coexposure to iron oxide nanoparticles (y-Fe2O3) - João Marcos de Lima Faria; Mariana Morozesk; Iara da Costa Souza; Victória Costa da Silva; Luiz Arthur Mendes Bataus; Simone Maria Teixeira de Sabóia-Morais; Marisa Narciso Fernandes (Aquatic Toxicology, 2025)

Taphonomic aspects of recent benthic foraminiferal assemblages, North Coast of the Sate of Bahia, Brazil - André Ramos Costa; Zelinda Margarida Andrade Nery Leão; Altair de Jesus Machado; Isabel Honorata de Souza Azevedo; Gabriela Santiago Mercês Pereira; Marlene Campos Peso-Aguiar; Simone Souza de Moraes (Journal of South American Earth Sciences, 2025)

Declines in coastal macrozooplankton communities within a recent climate and ocean tipping point in the Tropical South Atlantic - Denise Fabiana de Moraes Costa Schwamborn; Catarina da Rocha Marcolin; Nathália Lins-Silva; Morgana Brito-Lolaia; Humberto L. Varona; Simone Maria de Albuquerque Lira; Alexandre Oliveira de Almeida; Ralf Schwamborn (Science of The Total Environment, 2024)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Biomonitoring of firefighters' exposure to priority pollutant metal(loid)s during wildland fire combat missions: Impact on urinary levels and health risks - Ana Margarida Paiva; Bela Barros; Rui Azevedo; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; Maria do Carmo Pereira; João Paulo Teixeira; et al. (Science of The Total Environment, 2024)

Identification of candidate genes and genomic prediction for early heifer pregnancy in Nelore beef cattle - Elisa Peripolli; Larissa Bordin Temp; Heidge Fukumasu; Angelica Simone Cravo Pereira; Ester Costa Fabricio; José Bento Sterman Ferraz; Fernando Baldi (Livestock Science, 2024)

Supplementation of l-arginine in pregnant gilts affects the protein abundance of DNMT1 in 35-day fetuses - Karine Assis Costa; Lívia Maria dos Reis Barbosa; Daniele Botelho Diniz Marques; Walmir da Silva; Breno Soares Camilo; Domingos Lollobrigida de Souza Netto; Alysson Saraiva; José Domingos Guimarães; Simone Eliza Facioni Guimarães (Animal Reproduction Science, 2024)

A micro-scale insight into a back-arc trans-crustal plumbing system: The case of Marsili volcano, Southern Tyrrhenian Sea - Fabio Colle; Matteo Masotta; Simone Costa; Pier Paolo Giacomoni; Teresa Trua; Michael Marani (Lithos, 2024)

Typing of Treponema pallidum in a Brazilian sample and follow-up of treatment using molecular assays - Júlio Henrique Ferreira de Sá Queiroz; Tiago da Silva Ferreira; Kelle Cristhiane Soria Vieira Benedetti; Anny Danyelly da Costa Ribeiro; Ronaldo Omizolo de Souza; Simone Simionatto (Brazilian Journal of Microbiology, 2024)

Coastal plastic pollution: A global perspective - Beatriz Corrêa Thomé de Deus; Thaiane Cantarino Costa; Leslie Nascimento Altomari; Emília Marques Brovini; Paulo Sérgio Duque de Brito; Simone Jaqueline Cardoso (Marine Pollution Bulletin, 2024)

Lactation performance, feed efficiency, and blood metabolites of dairy cows treated with recombinant bovine somatotropin: A systematic review and meta-analysis - Ana Carolina Fluck; Fernando Reimann Skonieski; Kátia Maria Cardinal; Leonardo Piffer de Borba; Olmar Antônio Denardin Costa; Rodrigo Macagnan; Simone Stefanello; Ricardo Zambarda Vaz (Research in Veterinary Science, 2024)

Antimicrobial efficiency of bromhexine hydrochloride against endometritis-causing Escherichia coli and Trueperella pyogenes in bovines - Bruna Matzembacker; Dyeison da Silva Fantinel; Claudia Medeiros Rodrigues; Samara Pereira da Silva; Matheus Henrique Dal Bó Marin; Danillo Sales Rosa; Mateus Matiuzzi da Costa; Simone Silveira; Lilian Kolling Girardini (Brazilian Journal of Microbiology, 2024)

Biomonitoring of polycyclic aromatic hydrocarbons exposure and short-time health effects in wildland firefighters during real-life fire events - Ana Margarida Paiva; Bela Barros; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Klára Slezáková; João Paulo Teixeira; Solange Costa; Simone Morais (Science of The Total Environment, 2024)

Does the degradation of histosols due to recurrent fire affect the establishment of a hygrophilal autochthonous tree species? - Cristiane Coelho Moura; Simone Nunes Fonseca; Thaís Ribeiro Costa; Israel Marinho Pereira; Múcio Magno de Melo Farnezi; Jaçanan Eloisa de Freitas Milani; Darliana da Costa Fonseca; Gislene Carvalho Castro; Anne Priscila Dias Gonzaga; Luciana Coelho Moura; Evandro Luiz Mendonça Machado (Journal of Environmental Management, 2024)

The power of Posidonia oceanica meadows to retain microplastics and the consequences on associated macrofaunal benthic communities - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Fabio Badalamenti; Francesca Garaventa; Simone Mirto; Francesca Ape (Environmental Pollution, 2024)

Thiazolyl-isatin derivatives: Synthesis, in silico studies, in vitro biological profile against breast cancer cells, mRNA expression, P-gp modulation, and interactions of Akt2 and VIM proteins - Luiz Alberto Barros Freitas; Carolina Sousa; Beatriz Silva Lima; Denise Duarte; Paulo André Teixeira de Moraes Gomes; Camila Gabriela Costa Ramos; Valécia de Cássia Mendonça Costa; Maira Galdino da Rocha Pitta; Moacyr Jesus Barreto de Melo Rêgo; Carlos Alberto de Simone; Mafalda Videira; Ana Cristina Lima Leite (Chemico-Biological Interactions, 2024)

Benthic foraminifera as bioindicators in an area influenced by a submarine outfall, North Coast of Bahia, Brazil - André Ramos Costa; Zelinda Margarida Andrade Nery Leão; Altair de Jesus Machado; José Maria Landim Dominguez; Gabriela Santiago Mercês Pereira; Marlene Campos Peso Aguiar; Simone Souza de Moraes (Regional Studies in Marine Science, 2024)

A multi-step modelling approach to evaluate the fuel consumption, emissions, and costs in forest operations - Giulio Sperandio; Luciano Ortenzi; Raffaele Spinelli; Natascia Magagnotti; Simone Figorilli; Andrea Acampora; Corrado Costa (European Journal of Forest Research, 2024)

New and previously described species of Ameloblastella (Monogenoidea: Dactylogyridae) parasitizing Hypophthalmus marginatus and Pimelodina flavipinnis (Siluriformes: Pimelodidae) from the Tocantins River, Maranhão State, Brazil - Yuri Costa de Meneses; Marcia Cristina Nascimento Justo; Diego Carvalho Viana; Simone Chinicz Cohen (Systematic Parasitology, 2024)

An open-source machine-learning application for predicting pixel-to-pixel NDVI regression from RGB calibrated images - Lavinia Moscovini; Luciano Ortenzi; Federico Pallottino; Simone Figorilli; Simona Violino; Catello Pane; Valerio Capparella; Simone Vasta; Corrado Costa (Computers and Electronics in Agriculture, 2024)

Marine phycotoxin levels in shellfish—14 years of data gathered along the Italian coast - Stefano Accoroni; Monica Cangini; Roberto Angeletti; Carmen Losasso; Simone Bacchiocchi; Antonella Costa; Aurelia Di Taranto; Laura Escalera; Giorgio Fedrizzi; Angela Garzia; Francesca Longo; Andrea Macaluso; et al. (Harmful Algae, 2024)

Chemical, ecotoxicological, cytotoxic, and mutagenic evaluation of gelling agents used in the production of 70% alcohol gel - Natália Cristina de Oliveira D’Alessandro; Ryan Marques Rezende; João Antonio Xavier Manso; Dayane Cristina da Costa; Simone Maria Teixeira de Saboia-Morais; Daniela de Melo e Silva; Emmanuel Bezerra D′Alessandro; Hugo Freire Nunes; Nelson Roberto Antoniosi Filho (Environmental Toxicology and Pharmacology, 2024)

Bioherbicide potential of essential oils from plant species used in folk medicine and cuisine in the Amazon region - Joseila Maldaner; Fernanda Souza Silva; Darlisson de Alexandria Santos; Simone Yasue Simote Silva; Sebastião da Cruz Silva; Tatiane da Costa Lima; Selma L. Goulart; Bernardo Tomchinsky; Marilene Nunes Oliveira (South African Journal of Botany, 2023)

Development and properties of biodegradable film from peach palm (Bactris gasipaes) - Rebeca Desireé Sousa da Costa; Simone Hickmann Flôres; Adriano Brandelli; Carolina Galarza Vargas; Ana Carolina Ritter; Antonio Manoel da Cruz Rodrigues; Luiza Helena Meller da Silva (Food Research International, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Phytochemical analysis of Brugmansia suaveolens Bercht. & J. Presl and its therapeutic potential for topical use - Sandro Pinheiro da Costa; Raphaela Aparecida Schuenck-Rodrigues; Verônica da Silva Cardoso; Simone Sacramento Valverde; Alane Beatriz Vermelho; Eduardo Ricci-Júnior (Natural Product Research, 2023)

Concentrations of polycyclic aromatic hydrocarbons (PAHs) in liver samples of green turtles Chelonia mydas stranded in the Potiguar Basin, northeastern Brazil - Silmara Rossi; Daniel Solon Dias de Farias; Aline da Costa Bomfim; Renato S. Carreira; José Henrique Hildebrand Grisi-Filho; Carlos G. Massone; Flávio José de Lima Silva; Simone Almeida Gavilan (Marine Pollution Bulletin, 2023)

The use of an alimentary index to assess anthropogenic debris on green turtles (Chelonia mydas) - Daniel Solon Dias de Farias; Aline da Costa Bomfim Ventura; Flávio José de Lima Silva; Raquel Marinho de Souza Cavalcante; Silmara Rossi; Simone Almeida Gavilan; Vinícius Gabriel da Silva Santana; Viviane Souza do Amaral (Marine Pollution Bulletin, 2023)

Functional traits related to competition for light influence tree diameter increments in a biodiversity manipulation experiment - Raimondo Melis; Lourdes Morillas; Javier Roales; Jose M. Costa-Saura; Mauro Lo Cascio; Donatella Spano; Simone Mereu (European Journal of Forest Research, 2023)

Cardioprotective Effects of the 4-Week Aerobic Running Exercises Before Treatment with Doxorubicin in Rats - Talita Cristina Rodrigues Pereira; Thiago Montes Fidale; Lucas Costa Guimarães; Simone Ramos Deconte; Gustavo Cavinato Herrera; Antônio Vicente Mundim; Eduardo de Sales Cabral; Paulo Ricardo Lopes; Fernanda Rodrigues de Souza; Luiz Duarte de Ulhôa Rocha Júnior; Alinne Tatiane Faria Silva; Elmiro Santos Resende (Cardiovascular Toxicology, 2023)

Co-exposure of iron oxide nanoparticles with glyphosate herbicides in Poecilia reticulata: Fish liver damages is reversible during iron accumulation and elimination period - João Marcos de Lima-Faria; Victória Costa da Silva; Lee Chen Chen; Diego Stéfani Teodoro Martinez; Simone Maria Teixeira de Sabóia-Morais (Chemosphere, 2023)

Full genotype characterization of Brazilian canine G3P[3] strains during a 10-year survey (2012–2021) of rotavirus infection in domestic dogs and cats - Lais Sampaio Azevedo; Fernanda Faria Costa; Monique Beerens Abdul Ghani; Ellen Viana; Yasmin França; Roberta Salzone Medeiros; Raquel Guiducci; Simone Guadagnucci Morillo; Dieli Primo; Ricardo Duarte Lopes; Michele Soares Gomes-Gouvêa; Antonio Charlys da Costa; et al. (Archives of Virology, 2023)

Musa spp. cultivars as a neutralising source against some toxic activities of Bothrops and Crotalus genus snake venoms - Márcia Matos da Silva; Gerso Pereira Alexandre; Marta Regina Magalhães; Ana Maria Torres; Lucilia Kato; Victória Costa da Silva; Simone Maria Teixeira de Saboia Morais; Armando Garcia Rodriguez; Taícia Pacheco Fill; Alana Kelyene Pereira; Jussara Roque; Jorge Luiz Souza Simão; et al. (Toxicon, 2023)

Ovaries of guppies (Poecilia reticulata) investigated in pre-embryonic, embryonic and post-embryonic stages after exposure to maghemite nanoparticles (y-Fe2O3) associated with Roundup® and glyphosate, followed by recovery period evaluation - Victória Costa da Silva; João Marcos de Lima-Faria; Lucas Nunes Guimarães; Matheus Santos Costa; Phâmella Neres de Lima; Karina Simões; Lázaro Wender Oliveira de Jesus; Simone Maria Teixeira de Sabóia-Morais (Environmental Toxicology and Pharmacology, 2023)

Green tea and kombucha characterization: Phenolic composition, antioxidant capacity and enzymatic inhibition potential - Jordan Teixeira Oliveira; Fernanda Machado da Costa; Taiciane Gonçalvez da Silva; Greice Dotto Simões; Elisa dos Santos Pereira; Paola Quevedo da Costa; Robson Andreazza; Paulo Cavalheiro Schenkel; Simone Pieniz (Food Chemistry, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Strategies to improve the competitiveness of an agroindustrial system for a macauba based oil production in Minas Gerais State, Brazil - Pâmela da Costa Lima Pires; Aldara da Silva César; Alexandre Nunes Cardoso; Simone Palma Favaro; Marco Antonio Conejero (Land Use Policy, 2023)

Long non-coding RNA and circular RNA: new perspectives for molecular pathophysiology of atrial fibrillation - Ananília Medeiros Gomes da Silva; Marina Sampaio Cruz; Karla Simone Costa de Souza; Vivian Nogueira Silbiger (Molecular Biology Reports, 2023)

Endophytic species of Induratia from coffee and carqueja plants from Brazil and its potential for the biological control of toxicogenic fungi on coffee beans by means of antimicrobial volatiles - André Angelo Medeiros Gomes; Simone Albino Paes; Ana Paula Sato Ferreira; Danilo Batista Pinho; Zenilda de Lourdes Cardeal; Helvécio Costa Menezes; Patrícia Gomes Cardoso; Olinto Liparini Pereira (Brazilian Journal of Microbiology, 2023)

Lack of molecular evidence of fecal-borne viruses in capybaras from São Paulo state, Brazil, 2018–2020: a minor public health issue - Lais Sampaio de Azevedo; Yasmin França; Ellen Viana; Roberta Salzone Medeiros; Simone Guadagnucci Morillo; Raquel Guiducci; Cibele Daniel Ribeiro; Heloisa Rosa Vieira; Karolina Morales Barrio-Nuevo; Mariana Sequetin Cunha; Juliana Mariotti Guerra; Dulcilena de Matos Castro e Silva; et al. (Brazilian Journal of Microbiology, 2023)

Association between short-term exposure to air pollutants and cause-specific daily mortality in Italy. A nationwide analysis - Claudio Gariazzo; Matteo Renzi; Alessandro Marinaccio; Paola Michelozzi; Stefania Massari; Camillo Silibello; Giuseppe Carlino; Paolo Giorgi Rossi; Sara Maio; Giovanni Viegi; Massimo Stafoggia; Sandra Baldacci; et al. (Environmental Research, 2023)

CD14 signaling mediates lung immunopathology and mice mortality induced by Achromobacter xylosoxidans - Jefferson Elias-Oliveira; Morgana Kelly Borges Prado; Camila Oliveira Silva Souza; Marcella Roverato Pastore; Simone Gusmão Ramos; Ana Lúcia Costa Darini; Luiz Gustavo Gardinassi; Lúcia Helena Faccioli (Inflammation Research, 2022)

SARS-CoV-2 Omicron BA.1, BA.2, and XAG identification during routine surveillance on a university campus in Belo Horizonte, Brazil, 2022 - Daniel Costa Queiroz; Natália Virtude Carobin; Luiza Campos Guerra de Araújo e Santos; Paula Luize Camargos Fonseca; Isabela Lorraine Braga-Paz; Rillery Calixto Dias; Jorge Gomes Goulart Ferreira; Túlio Resende Freitas; Diego Menezes; Sílvia Cristina Verde Mendes Nolasco; Simone Rodrigues Ribeiro; Thaís Salviana Ribeiro; et al. (Brazilian Journal of Microbiology, 2022)

Chicken embryos are a valuable model for the selection of Bacillus subtilis for probiotic purposes - Thais Fernanda Martins dos Reis; Patricia Giovana Hoepers; Vasco Ariston de Carvalho Azevedo; Gabriela Ribeiro da Silva; Fabiana Oliveira Notário; Maria Cecília Soares; André Eduardo Schlemper; Ícaro Mendonça Costa; Nina Dias Coelho-Rocha; Mylla Spirandelli da Costa; Simone Sommerfeld; Alessandra Aparecida Medeiros-Ronchi; et al. (Archives of Microbiology, 2022)

Heritability and genetic correlations between marbling in longissimus dorsi muscle and conventional economic traits in Nellore beef cattle - Marisol Londoño-Gil; Daniel Cardona-Cifuentes; Juan Diego Rodríguez; Ludmilla Costa Brunes; Claudio Ulhoa Magnabosco; Angelica Simone Cravo Pereira; Elisa Peripolli; Raysildo Barbosa Lôbo; Fernando Baldi (Tropical Animal Health and Production, 2022)

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Effect of a reservoir network on drought propagation in a semi-arid catchment in Brazil - Simone C. H. van Langen; Alexandre C. Costa; Germano G. Ribeiro Neto; Pieter R. van Oel (Hydrological Sciences Journal, 2021)

Inoculation with isolates of arbuscular mycorrhizal fungi influences growth, nutrient use efficiency and gas exchange traits in micropropagated apple rootstock ‘Marubakaido’ - Murilo Dalla Costa; Tássio Dresch Rech; Silmar Primieri; Bruna Greicy Pigozzi; Simone Silmara Werner; Sidney Luiz Stürmer (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Viability of the use of mycotoxin adsorbent in the finishing of Texel lambs in confinement - Fabiola Cristine de Almeida Rego; Pedro Leonardo Olszewski Savio; Simone Fernanda Nedel Pertile; Joice Sifuentes dos Santos; Josiane Ito Eleodoro; Alfredo Jorge Costa Teixeira; Marilice Zundt; Luiz Fernando Coelho da Cunha Filho; José Victor Pronievicz Barreto (Tropical Animal Health and Production, 2021)

Understanding community perceptions of an urban stream before and after a discussion of revitalization possibilities using photo-elicitation - Simone Lima da Costa Preuss; Jaime Joaquim da Silva Pereira Cabral; Angus Morrison-Saunders; Mike Hughes; Ana Bárbara de Araújo Nunes (Environment, Development and Sustainability, 2021)

Evaluation of climate simulations produced with the Brazilian global atmospheric model version 1.2 - Caio A. S. Coelho; Dayana C. de Souza; Paulo Y. Kubota; Simone M. S. Costa; Layrson Menezes; Bruno S. Guimarães; Silvio N. Figueroa; José P. Bonatti; Iracema F. A. Cavalcanti; Gilvan Sampaio; Nicholas P. Klingaman; Jessica C. A. Baker (Climate Dynamics, 2021)

COS-7 cells are a cellular model to monitor polyomavirus JC miR-J1-5p expression - Simone Agostini; Roberta Mancuso; Andrea Saul Costa; Franca Rosa Guerini; Mario Clerici (Molecular Biology Reports, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Global Deep-Sea Biodiversity Research Trends Highlighted by Science Mapping Approach - Corrado Costa; Emanuela Fanelli; Simone Marini; Roberto Danovaro; Jacopo Aguzzi (Frontiers in Marine Science, 2020)

Amino Acids as Stress Reducers in Soybean Plant Growth Under Different Water-Deficit Conditions - Walquíria Fernanda Teixeira; Luís Henrique Soares; Evandro Binotto Fagan; Simone da Costa Mello; Klaus Reichardt; Durval Dourado-Neto (Journal of Plant Growth Regulation, 2020)

Connectivity Between Coastal and Oceanic Zooplankton From Rio Grande do Norte in the Tropical Western Atlantic - Sigrid Neumann Leitão; Mauro de Melo Junior; Fernando de Figueiredo Porto Neto; Andréa Pinto Silva; Xiomara Franchesca Garcia Diaz; Tamara de Almeida e Silva; Dilma Aguiar do Nascimento Vieira; Lucas Guedes Pereira Figueiredo; Alejandro Esteweson Santos Faustino da Costa; Jana Ribeiro de Santana; Renata Polyana de Santana Campelo; Pedro Augusto Mendes de Castro Melo; et al. (Frontiers in Marine Science, 2019)

A height-wood-seed axis which is preserved across climatic regions explains tree dominance in European forest communities - José M. Costa-Saura; Antonio Trabucco; Donatella Spano; Simone Mereu (Plant Ecology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Science mapping approach to analyze the research evolution on precision agriculture: world, EU and Italian situation - Federico Pallottino; Marcello Biocca; Pierfrancesco Nardi; Simone Figorilli; Paolo Menesatti; Corrado Costa (Precision Agriculture, 2018)

Anacardic Acids from Cashew Nuts Prevent Behavioral Changes and Oxidative Stress Induced by Rotenone in a Rat Model of Parkinson’s Disease - Cybelle Façanha Barreto Medeiros-Linard; Belmira Lara da Silveira Andrade-da-Costa; Ricielle Lopes Augusto; Adriana Sereniki; Maria Teresa Sales Trevisan; Renata de Cássia Ribas Perreira; Francisco Thiago Correia de Souza; Glauber Ruda Feitoza Braz; Claudia Jacques Lagranha; Ivone Antônia de Souza; Almir Gonçalves Wanderley; Soraya S. Smailli; et al. (Neurotoxicity Research, 2018)

Paleolimnological records reveal biotic homogenization driven by eutrophication in tropical reservoirs - Simone Wengrat; Andre A. Padial; Erik Jeppesen; Thomas A. Davidson; Luciane Fontana; Sandra Costa-Böddeker; Denise C. Bicudo (Journal of Paleolimnology, 2018)

Carnosic Acid Suppresses the H2O2-Induced Mitochondria-Related Bioenergetics Disturbances and Redox Impairment in SH-SY5Y Cells: Role for Nrf2 - Marcos Roberto de Oliveira; Gustavo da Costa Ferreira; Alessandra Peres; Simone Morelo Dal Bosco (Molecular Neurobiology, 2018)

The invisibility of fisheries in the process of hydropower development across the Amazon - Carolina Rodrigues da Costa Doria; Simone Athayde; Elineide E. Marques; Maria Alice Leite Lima; Jynessa Dutka-Gianelli; Mauro Luis Ruffino; David Kaplan; Carlos E. C. Freitas; Victoria N. Isaac (Ambio, 2017)

Carnosic Acid Protects Mitochondria of Human Neuroblastoma SH-SY5Y Cells Exposed to Paraquat Through Activation of the Nrf2/HO-1Axis - Marcos Roberto de Oliveira; Alessandra Peres; Gustavo Costa Ferreira; Patrícia Fernanda Schuck; Clarissa S. Gama; Simone Morelo Dal Bosco (Molecular Neurobiology, 2017)

Carnosic Acid Affords Mitochondrial Protection in Chlorpyrifos-Treated Sh-Sy5y Cells - Marcos Roberto de Oliveira; Alessandra Peres; Gustavo Costa Ferreira; Patrícia Fernanda Schuck; Simone Morelo Dal Bosco (Neurotoxicity Research, 2016)

Environmental Surveillance of Polioviruses in Rio de Janeiro, Brazil, in Support to the Activities of Global Polio Eradication Initiative - Joseane Simone de Oliveira Pereira; Lidiane Rodrigues da Silva; Amanda de Meireles Nunes; Silas de Souza Oliveira; Eliane Veiga da Costa; Edson Elias da Silva (Food and Environmental Virology, 2016)

Clozapine linked to nanocapsules minimizes tissue and oxidative damage to biomolecules lipids, proteins and DNA in brain of rats Wistar - Angélica Aparecida da Costa Güllich; Ritiéle Pinto Coelho; Bruna Cocco Pilar; Deise Jaqueline Ströher; Leandro Alex Sander Leal Galarça; Simone Machado Vieira; Jacqueline da Costa Escobar Piccoli; Sandra Elisa Haas; Vanusa Manfredini (Metabolic Brain Disease, 2015)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Monitoring Mercury Exposure in Reproductive Aged Women Inhabiting the Tapajós River Basin, Amazon - Tereza Cristina de Oliveira Corvelo; Érika Abdon Fiquene Oliveira; Amanda Magno de Parijós; Claudia Simone Baltazar de Oliveira; Rosane do Socorro Pompeu de Loiola; Amélia A. de Araújo; Carlos Araújo da Costa; Luiz Carlos de Lima Silveira; Maria da Conceição Nascimento Pinheiro (Bulletin of Environmental Contamination and Toxicology, 2014)

Impaired mitochondrial function and reduced viability in bone marrow cells of obese mice - Genilza Pereira de Oliveira; Erika Cortez; Graça Justo Araujo; Katia Costa de Carvalho Sabino; Fabiana Alves Neves; Amélia Faustino Bernardo; Simone Nunes de Carvalho; Anibal Sanchez Moura; Laís Carvalho; Alessandra Alves Thole (Cell and Tissue Research, 2014)

Stigma Diversity in Tropical Legumes with Considerations on Stigma Classification - Marina Fernanda Bortolin Costa; Juliana Villela Paulino; Cristina Ribeiro Marinho; Viviane Gonçalves Leite; Giseli Donizete Pedersoli; Simone Pádua Teixeira (The Botanical Review, 2014)

A phosphoramidon-sensitive metalloprotease induces apoptosis of human endothelial cells by Group B Streptococcus - Michelle Hanthequeste Bittencourt dos Santos; Andréia Ferreira Eduardo da Costa; Beatriz Jandre Ferreira; Simone Lima Souza; Pamella da Silva Lannes; Gabriela Silva Santos; Ana Luiza Mattos-Guaraldi; Prescilla Emy Nagao (Antonie van Leeuwenhoek, 2013)

Regionalization of the GOES-10 retrieval algorithm for tropical South America - Weber Andrade Gonçalves; Simone Sievert Costa; Carlos Frederico de Angelis; Jurandir Ventura Rodrigues; Rodrigo Augusto Ferreira de Souza (International Journal of Remote Sensing, 2012)

Double-phase culture system for large scale production of pineapple - Jonny E. Scherwinski-Pereira; Elequisandra da C. Araruna Lima; Tatiane L. da Silva; Antonio G. Gomes Mesquita; Simone de A. Maciel; Frederico H. da Silva Costa (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Ground-based single-frequency microwave radiometric measurement of water vapour - P. K. Karmakar; M. Maiti; Alan James P. Calheiros; Carlos Frederico Angelis; Luiz Augusto Toledo Machado; Simone Sievert Da Costa (International Journal of Remote Sensing, 2011)

Differential gene regulation in potato cells and plants upon abrupt or gradual exposure to water stress - Alfredo Ambrosone; Antonello Costa; Rosanna Martinelli; Immacolata Massarelli; Vincenzo De Simone; Stefania Grillo; Antonella Leone (Acta Physiologiae Plantarum, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Erratum to: Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Mutagenic and Genotoxic Effects of cis-(Dichloro)tetraammineruthenium(III) Chloride on Human Peripheral Blood Lymphocytes - Alessandra de Santana Braga Barbosa Ribeiro; Cláudio Carlos da Silva; Flávia de Castro Pereira; Aliny Pereira de Lima; Cesar Augusto Sam Tiago Vilanova-Costa; Simone Santos Aguiar; Luiz Alfredo Pavanin; Aparecido Divino da Cruz; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2009)

Innate immunity to Paracoccidioides brasiliensis infection - Vera Lúcia Garcia Calich; Tânia Alves da Costa; Maíra Felonato; Celina Arruda; Simone Bernardino; Flávio Vieira Loures; Laura Raquel Rios Ribeiro; Rita de Cássia Valente-Ferreira; Adriana Pina (Mycopathologia, 2008)

Evaluation of levels, sources and distribution of toxic elements in PM10 in a suburban industrial region, Rio de Janeiro, Brazil - Vitor Eugênio Toledo; Pierre Batista de Almeida Júnior; Simone Lorena Quiterio; Graciela Arbilla; Andréa Moreira; Viviane Escaleira; Josino Costa Moreira (Environmental Monitoring and Assessment, 2008)

Susceptibility of Human Pathogenic Bacteria to Antimicrobial Peptides from Sesame Kernels - Fábio Teles Costa; Simone Maria Neto; Carlos Bloch; Octávio Luiz Franco (Current Microbiology, 2007)

Polycyclic Aromatic Hydrocarbons and their Molecular Diagnostic Ratios in Airborne Particles (PM10) Collected in Rio de Janeiro, Brazil - Simone Lorena Quiterio; Graciela Arbilla; Glauco Favilla Bauerfeldt; Josino Costa Moreira (Water, Air, & Soil Pollution, 2007)

Evolutionary chromosomal differentiation among four species of Conoderus Eschscholtz, 1829 (Coleoptera, Elateridae, Agrypninae, Conoderini) detected by standard staining, C-banding, silver nitrate impregnation, and CMA3/DA/DAPI staining - Marielle Cristina Schneider; Mara Cristina Almeida; Simone Policena Rosa; Cleide Costa; Doralice Maria Cella (Genetica, 2006)

RNA interference: ready to silence cancer? - Simone Mocellin; Rodolfo Costa; Donato Nitti (Journal of Molecular Medicine, 2006)